Los gimnosofistas indios como modelos del sabio asceta para cínicos y cristianos - Oliver Segura, Juan Pedro (Antigüedad y Cristianismo, 1990)
The Greeks met for the first time the Indian ascetics, whom they called «gimnosophists », during the expedition of Alexander. The cynic Onesicrito was the first to manipulate the image of the gimnosophists when he put in the mouth of these ascetics the idealisms of the cynics. The supposed meeting of Alexander with the gimnosophists evolves from a simple anecdote into a long dialogue (cf. Pap. genev. 271), in which —encratic— doctrines of a gnostic sect which preached asccetism, come to light. This dialogue became very popular when it was included in The Life of Alexander of Macedón by Pseudo-Callisthenes. Later the bishop Paladio used the figure of the gimnosophists to give prestige to the anacoretes that lived in the Egyptian desert; but it also was used in the COLLATIO to make fun of the extremisms of the Christian monks.